The effectiveness of teaching aids in providing secondary school students Elements of artwork (Journal of the College of Basic Education, 2019)
This study aims at 1- Designing teaching plans for the elements of the technical work to develop the technical skills of secondary school students - second grade and using the appropriate educational means. 2- Measuring the effectiveness of the teaching plans. The researcher used the experimental method with the minimum set of control، called the design of one group with both pre and post tests. The researcher prepared the research tool of the cognitive achievement test consisting of (30) questions. D was characterized by honesty and consistency، and a skill test consisting of (6) questions as well as the researcher designed a form to evaluate the skill performance، and the experiment lasted (4) weeks and after the application of the tool and the use of statistical methods in data processing showed the results of statistical differences in favor of the post-test and this result Confirms the effectiveness of the content of the teaching plans prepared in the current research in the development of skills for students of the second intermediate grade، with regard to the technical skills of the elements of the art work included in the art education subject as it was able to achieve compatibility between ideas، concepts and theoretical information presented In a practical lesson plans and practices that can be applied to their performance observed in the implementation of the requirements of the content of this article، and through the search results researcher presented a number of recommendations and proposals. Including: Adoption of teaching plans designed in the current research in the relevant educational institutions in which the study of the elements of art work to prove its effectiveness and its ability to develop students' technical skills.